Student Characteristics in Culinary Vocational Schools for Contextual and Entrepreneurship-Based Science Learning - Asrorul Azizi; A. Wahab Jufri; Muhammad Sarjan; Yunita Arian Sani Anwar (Lembaga Bale Literasi, 2026)
This study aims to analyze the characteristics of students of a State Vocational High School (SMK) culinary program on Lombok Island as a basis for developing contextual and entrepreneurial-oriented science learning in the subject of